Information Technology in Tourism Management: A Decade Bibliometric Analysis - Suardana, I Ketut; Adiyanti, Assyifa Shafia; Widodo, Wahyu Indro; Anggraini, Fera Dhian; Novianti, Nina; Dewi, Winda Rosita; Nurman, Neneng Nurhayati (Journal of Information Systems Research and Practice, 2024)
This paper presents a bibliometric analysis of Information Technology (IT) literature in tourism management over the past decade, aiming to identify trends and guide future research. Using visual analysis tools like VOSviewer and data from the Scopus database, the study focuses on research publications on Sustainable Tourism Village Development Strategies from 2014-2024. Findings reveal 1181 documents, with China, Spain, India, and the United States leading in publications. Key subject areas include Computer Science, Business, Management, Accounting, Economics, and Environmental Science. Co-authorship networks highlight collaborative efforts, with prominent contributors including Universitat Politècnica de València and Bina Nusantara University. Analysis of research keywords and clusters emphasizes technology’s crucial role in shaping the tourism sector and fostering interdisciplinary collaboration. This study offers insights for leveraging technology effectively, enhancing competitiveness, and promoting sustainable tourism development.